2019
DOI: 10.1103/physrevd.100.055030
|View full text |Cite
|
Sign up to set email alerts
|

Complete vectorlike fourth family and new U(1) for muon anomalies

Abstract: We consider the Standard Model (SM) with the addition of a U(1) gauge symmetry and a complete fourth family of quarks and leptons which are vector-like with respect to the full SU(3) C × SU(2) L × U(1) Y × U(1) gauge symmetry. The model provides a unified explanation of experimental anomalies in (g − 2) µ as well as b → s + − decays. We find good fits to the deviations from the SM, while at the same time fitting all other SM observables. The model includes a new Z gauge boson, a U(1) -breaking scalar, and vect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 198 publications
(199 reference statements)
2
28
0
Order By: Relevance
“…In an attempt to distinguish these two possibilities, one might focus on a cluster of discrepancies which can all be resolved with the same new physics. This is what we have done in a previous letter [1]. We have shown that the muon anomalies associated with the anomalous magnetic moment of the muon, ∆a µ , and the angular and lepton non-universality anomalies in b → s + − decays can simultaneously be resolved by the addition to the SM of a complete vector-like (VL) family of quarks and leptons together with a new U(1) gauge symmetry carried only by the new VL states.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…In an attempt to distinguish these two possibilities, one might focus on a cluster of discrepancies which can all be resolved with the same new physics. This is what we have done in a previous letter [1]. We have shown that the muon anomalies associated with the anomalous magnetic moment of the muon, ∆a µ , and the angular and lepton non-universality anomalies in b → s + − decays can simultaneously be resolved by the addition to the SM of a complete vector-like (VL) family of quarks and leptons together with a new U(1) gauge symmetry carried only by the new VL states.…”
Section: Introductionsupporting
confidence: 83%
“…As already discussed in more detail in [1], the U(1) gauge coupling g diverges at a Landau pole at the scale…”
Section: Landau Pole Constraints On the U(1) Gauge Couplingmentioning
confidence: 60%
See 1 more Smart Citation
“…The µ-e conversion process in nuclei induced by flavons might be detectable [142]. The conversion rate is given by [150,151], [160].…”
Section: Lepton Flavor Violationmentioning
confidence: 99%
“…We employed the same constant values of the SM contributions and the hadronic matrix elements as in Ref. [160]. Their values relevant to our analysis are shown in Table 4.…”
Section: Quark Flavor Violationmentioning
confidence: 99%